The first rule : a Joe Pike novel - Crais, Robert (New York : G. P. Putnam's Sons, 2010)
Frank Meyer had the American dream-until the day a professional crew invaded his home and murdered everyone inside. The police think Meyer was hiding something very bad, but Joe Pike does not. With the help of Elvis Cole, Pike sets out on a hunt of his own--an investigation that quickly entangles them both in a web of ancient grudges, blood ties, blackmail, vengeance, double crosses, and cutthroat criminals.
National College of Business and Arts
Keywords: Married people -- Crimes against -- Fiction; Detective and mystery fiction